Pharmacokinetics/pharmacodynamics of polymyxin B in patients with bloodstream infection caused by carbapenem-resistant Klebsiella pneumoniae - Yu, Zhenwei; Liu, Xiaofen; Du, Xiaoxing; Chen, Huiying; Zhao, Feng; Zhou, Zhihui; Wang, Yu; Zheng, Yang; Bergen, Phillip J.; Li, Xi; Sun, Renhua; Fang, Li; et al. (Frontiers in Pharmacology, 2022)
Polymyxin B is a last-line therapy for carbapenem-resistant microorganisms. However, a lack of clinical pharmacokinetic/pharmacodynamic (PK/PD) data has substantially hindered dose optimization and breakpoint setting. A prospective, multi-center clinical trial was undertaken with polymyxin B (2.5 mg/kg loading dose [3-h infusion], 1.25 mg/kg/12h maintenance dose [2-h infusion]) for treatment of carbapenem-resistant K. pneumoniae (CRKP) bloodstream infections (BSI). Safety, clinical and microbiological efficacy were evaluated. A validated LC-MS/MS method was applied to determine the concentrations of polymyxin B in blood samples. Population PK modeling and Monte Carlo simulations were conducted to examine the susceptibility breakpoint for polymyxin B against BSI caused by CRKP. Nine patients were enrolled and evaluated for safety. Neurotoxicity (5/9), nephrotoxicity (5/9), and hyperpigmentation (1/9) were recorded in 8/9 patients. Blood cultures were negative within 3 days of commencing therapy in all 8 patients evaluated for microbiological efficacy, and clinical cure or improvement occurred in 6 of 8 patients. Cmax and Cmin following the loading dose were 5.53 ± 1.80 and 1.62 ± 0.41 mg/L, respectively. With maintenance dosing, AUCss,24h was 79.6 ± 25.0 mg·h/L and Css,avg 3.351.06 mg/L. Monte Carlo simulations indicated that a 1 mg/kg/12-hourly maintenance dose could achieve >90% probability of target attainment (PTA) for isolates with MIC ≤1 mg/L. PTA dropped substantially for MICs ≥2 mg/L, even with a maximally recommended daily dose of 1.5 mg/kg/12-hourly. This is the first clinical PK/PD study evaluating polymyxin B for BSI. These results will assist to optimize polymyxin B therapy and establish its breakpoints for CRKP BSI.